2023
DOI: 10.1371/journal.pone.0283966
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of the Shannon entropy for mass spectrometry imaging

Abstract: Mass spectrometry imaging (MSI) allows us to visualize the spatial distribution of molecular components in a sample. A large amount of mass spectrometry data comprehensively provides molecular distributions. In this study, we focus on the information in the obtained data and use the Shannon entropy as a quantity to analyze MSI data. By calculating the Shannon entropy at each pixel on a sample, the spatial distribution of the Shannon entropy is obtained from MSI data. We found that low-entropy pixels in entropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Higher audio entropy indicates greater variability in audio sample values, potentially suggesting more complex or random sounds. Conversely, lower entropy implies that the sound tends to have patterns or repetitions, with less variation in sample values [27].…”
Section: Entropy Voice Encryption Analysismentioning
confidence: 99%
“…Higher audio entropy indicates greater variability in audio sample values, potentially suggesting more complex or random sounds. Conversely, lower entropy implies that the sound tends to have patterns or repetitions, with less variation in sample values [27].…”
Section: Entropy Voice Encryption Analysismentioning
confidence: 99%
“…In [20], a method based on the information entropy (Shannon entropy) for time-of-flight secondary ion mass spectrometry (TOF-SIMS) was proposed and it was shown that without peak identification the spatial distribution (heat maps) of the Shannon entropy of spectra indicates differences in materials and changes in the conditions of a material in a sample. The spatial distribution of the Shannon entropy was also studied for the matrix-assisted laser desorption/ionization (MALDI) MSI and a method to select candidate peaks was proposed [21].…”
Section: Introductionmentioning
confidence: 99%